Construction of Synthetic Promoters by Assembling the Sigma Factor Binding −35 and −10 Boxes. Issue 1 (7th December 2018) - Wang, Yang; Liu, Qingtao; Weng, Huanjiao; Shi, Yanan; Chen, Jian; Du, Guocheng; Kang, Zhen
Abstract : Promoter is one of the key elements in regulating gene expression. Many natural or synthetic promoters have been modulated by their cis ‐ or tans ‐regulatory elements to confer instant gene expression change in responding to designated stimuli. In addition, bacterial cells also engage different sigma factors to control the gene expression network at different growth phases or in response to the changing environment and external stresses. In this study, a set of promoters that assimilate the endogenous regulation of different sigma factors σ 70, σ 38, σ 32, and σ 24 are synthesized. Promoters are designed to contain two or more kinds of interlocking sigma factor binding sites. The most competitive sigma factors will be automatically selected by the cell to take over the synthetic promoters during the cell growth course. Some of the synthetic promoters exhibit very strong strengths under different conditions, including stationary phase, low temperature, acidic pH, and high osmotic pressure. Comparing to the T7 promoter, synthetic promoter P21285 achieved higher yields of L‐asparaginase and acid urease in Escherichia coli . The research not only expands the synthetic biology toolbox but also provide another strategy to design and construct synthetic promoters in prokaryotes. Abstract : Most prokaryotic promoters have a single type sigma factor binding site and are therefore transcriptionally controlled by a single sigma factor. In this study, synthetic promoters by interlocking different sigma factor binding sites are designed. The most competitive sigma factors will be automatically selected by the cell to control the synthetic promoters. By assimilating the endogenous regulation of different sigma factors, some of the synthetic promoters exhibit very stable and strong strengths under different growth conditions.